2021
DOI: 10.1590/s1677-5538.ibju.2020.0017
|View full text |Cite
|
Sign up to set email alerts
|

Can platelet-rich plasma coating improve polypropylene mesh integration? An immunohistochemical analysis in rabbits

Abstract: Purpose: Despite high success rates in the treatment of urinary incontinence, complications related to the use of polypropylene (PP) meshes are still a concern, especially in vaginal prolapses surgeries. The objective of this study was to assess the effect of autologous platelet-rich plasma (PRP) coating on the integration of PP meshes implanted in the vaginal submucosa of rabbits. Materials and Methods: Thirty adult New Zealand rabbits were randomly divided into two groups (n=15): PP, implanted with conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Up ]. Despite the fact that both groups presented significant morphological variations in muscle spindles compared to rats without SUI, the PRP group had lower variations than the control one [14 ]. The pilot study by Behnia-Wilson et al was the first observational study that investigated the effect of PRP in the management of SUI by applying a combination of PRP and CO 2 micro-ablative laser in 62 patients with SUI [15].…”
Section: Platelet Rich Plasma and Stress Urinary Incontinencementioning
confidence: 99%
See 2 more Smart Citations
“…Up ]. Despite the fact that both groups presented significant morphological variations in muscle spindles compared to rats without SUI, the PRP group had lower variations than the control one [14 ]. The pilot study by Behnia-Wilson et al was the first observational study that investigated the effect of PRP in the management of SUI by applying a combination of PRP and CO 2 micro-ablative laser in 62 patients with SUI [15].…”
Section: Platelet Rich Plasma and Stress Urinary Incontinencementioning
confidence: 99%
“…In the field of mesh surgery, preliminary in vitro and animal studies have also shown encouraging outcomes in improving the postoperative outcomes after the use of meshes coated with PRP [4 ▪▪ ]. The randomized experimental study by Dias et al evaluated the impact of PRP-coated polypropylene meshes compared to noncoated ones implanted in rabbit's vaginal submucosa [22 ▪ ]. A significantly elevated CD-31 angiogenesis marker was observed in favor of PRP group compared to control ( P < 0.0001 ) while inflammatory markers including interluekin-13, TGF-β and TNF-α did not differ among the two groups [22 ▪ ].…”
Section: Historical Data and Current Landscapementioning
confidence: 99%
See 1 more Smart Citation